Promoting Tax Compliance in the Democratic Republic of Congo: Lessons Learned from the Republic of Korea as Case Study - BIMBALA GWABA, Joseph; Kim, Yun-Seon; Pambi Tadiamba, Augustin; Ngwaba, Jacob; Ntiama, Junior; MBIMBI, Justin; You, SongHee; Cho, Kwanphil; Yoo, Keedong (International JOURNAL OF CONTENTS, 2024)
Tax revenues are primary sources of funding for public expenditure in most developing countries. Therefore, tax administration as a focal point of economic policies should receive keen attention. This raises the following important questions: 1) what constitutes an efficient tax system? and 2) how can the tax system be designed to generate optimal revenue to finance public spending and promote economic development? Many developed countries, including the United States, Canada, South Korea, and China, have made significant efforts to establish effective tax management systems using available solutions. According to official reports from international organizations, African countries generally rank poorly in tax sector management. Challenges include inefficient tax collection methods, structural and functional complexities, lack of a tax culture, and crucially, underutilization of information technology as a tool to modernize the tax system. This paper strongly encourages developing countries to learn from achievements and best practices of other countries rather than reinventing the wheel. It specifically analyzes the existing tax management system of the Democratic Republic of Congo (DRC), provides a comprehensive review of the Korean tax system, and summarizes key lessons learned. A critical assessment of organizational, functional, and structural challenges was carried out using analytical and descriptive methodologies. The case study of South Korea is particularly insightful. The design of Korea's tax system reflects its unique structure, function, and policy goals, which have evolved in tandem with its economic development policies. However, the author advises caution when considering Korean fiscal policies due to their unique contexts. This paper proposed a customized tax framework for the DRC, which could also be applicable to other developing countries. KCI Citation Count: 0